2015
DOI: 10.7567/apex.8.045802
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and electronic structures for B-doped bulk and surface AlN: Ab initio calculations

Abstract: The magnetism and electronic structures for B-doped bulk and surface AlN are investigated. Our calculations show that the 6.25% B-doped AlN is a half-metallic ferromagnet with a 0.851 eV half-metallic gap. Under an Al-rich condition, the formation energy is 3.83 eV, indicating that the Bdoped AlN could be realized experimentally. Electronic structures show that a double-exchange mechanism plays an important role in forming the ferromagnetism. Nitrogen vacancy, emerging in B-doped AlN, would result in a total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Hence, it is already used in photoelectronics, [13] optics, [14] electronics, [15,16] and spintronics. [17][18][19][20][21][22][23] In particular, the AlNbased dilute magnetic semiconductor material is considered as the most promising candidate for future spintronic and spinmagnetic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is already used in photoelectronics, [13] optics, [14] electronics, [15,16] and spintronics. [17][18][19][20][21][22][23] In particular, the AlNbased dilute magnetic semiconductor material is considered as the most promising candidate for future spintronic and spinmagnetic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] So much effort has been invested in exploring the effects of nonmagnetic element dopants. Fan et al [27] revealed that substituting B for N can produce magnetization, and a double-exchange mechanism is important in forming the ferromagnetism. Bai et al [28] demonstrated that Be and C dopants can produce local spin states, resulting in a magnetic moment of 1.00µ B .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Among them, the AlN nanosheet has received considerable attention of researchers from the field of optics, electronics, photoelectronics and spintronics, for it enjoys the same honeycomb lattice structure as graphene and possesses outstanding properties. [14][15][16][17][18][19][20][21][22][23][24][25] In the field of spin electronics and magnetic devices, the AlN-based dilute magnetic semiconductor material is the most promising candidate. However, this pristine 2D material has no intrinsic magnetism as a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Given the high cost of the experimental fabrication and characterization of materials, the establishment of the candidate pool based on high-accuracy computations is a more efficient and economic approach to discover novel half-metals. Indeed, theoretical studies have predicted the existence of a series of half-metals [14][15][16][17][18] and some of them were experimentally confirmed later. 19 The metal-organic frameworks (MOFs), which are made by linking metal nodes with organic ligands through strong bonds, have many potential applications in the fields of nanoscience and nanotechnology since they offer specific advantages owing to tunable pore metrics for ion transport, tunable electronic properties, high surface areas, high density of active catalytic sites, and quantum size effect.…”
Section: Introductionmentioning
confidence: 93%